New molecular markers for the study of tumour lymphangiogenesis. - Jackson, D (2001)
The capacity of malignant tumours to metastasize to distant tissues presents a huge problem for the treatment of cancers using conventional surgical and cytotoxic drug therapies. One of the main routes for tumour spread is via the lymphatic vessels, an important conduit for tumours such as breast, lung and gastrointestinal tract that frequently colonize regional lymph nodes. In comparison with the vasculature however, little is known about the biology of tumour lymphatics, tumour lymphangiogenesis or the mechanisms that regulate entry and subsequent migration of tumour cells within lymphatic vessels. This situation has persisted because of the lack of specific molecular markers with which to visualize even normal lymphatics within tissues or to isolate lymphatic endothelial cells for in vitro experimental analysis. Just recently however, novel markers for lymphatic endothelial cells have been identified and their availability has revolutionized research in this field. In this article we highlight the main characteristics of these markers and review recent progress in their use to study tumour lymphangiogenesis.